Spiritual Interventions in Veterans with PTSD: A Systematic Review - Smothers, Zachary P. W. (Journal of religion and health, 2018)
This article reports the results of a systematic review on the effectiveness of religious/spiritually (R/S)-based interventions in veterans with post-traumatic stress disorder (PTSD). A total of 385 unique records were identified with eight meeting the inclusion criteria. Seven studies reported significant improvement in reported outcome measures demonstrating the effectiveness of R/S-based interventions in PTSD, with the eighth study reporting positive improvements. We conclude that the few existing published studies report significant benefits to veterans on several outcomes. R/S interventions for veterans with PTSD need to be further developed and tested to determine their efficacy and safety.